Optimizing the Learning with “Smart Learning” for Special Needs Children in Inclusive School: Optimalisasi Pembelajaran dengan “Smart Learning” Untuk Anak Berkebutuhan Khusus di Sekolah Inklusi - Seri Hartati; Nurul Aiyuda; Luluk Elvitaria (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service was carried out at the inclusive school X in Pekanbaru involving all Children with Special Needs. Children with Special Needs or commonly called ABK is a term for children who have physical, mental, social, or emotional conditions that are different from children in general. The use of the "Smart Learning" method which is optimized for children with special needs in inclusive schools is urgently needed to facilitate learning. This service involves collaboration between research teams, inclusive teachers, and principal to design, develop, and test the effectiveness of adaptive learning models that use information and communication technology (ICT). This "Smart Learning" method is specifically adapted to facilitate an inclusive learning process, taking into account the learning needs and preferences of each student. The method is carried out with the stages of observation, implementation and evaluation by presenting pre and post test surveys to find out the effectiveness of learning. The results of the post test show that the application of "Smart Learning" to children with special needs in inclusive schools can increase their active participation, motivate and increase their academic achievement